PENYUSUNAN LAPORAN KEUANGAN MASJID (STUDI KASUS MUHAMMADIYAH AL-MUHAJIRIN DAN MASJID JAMI PEMURUS DALAM) - Fadhillah, Rizky; Ainun, Basyirah; Andriani, Andriani; Sadewa, Manik Mutiara (Jurnal IMPACT: Implementation and Action, 2024)
Mosques are institutions that collect and distribute community funds, therefore it is necessary to carry out financial records in accordance with generally accepted standards for mosques. PSAK 1 and ISAK 35 are relevant financial reports for reporting mosque financial flows. In this activity, the objects were the Muhammadiyah Al-Muhajirin Mosque in Banjarmasin and the Jami Pemurus Dalam Mosque. Through technical guidance by direct visits to the field, results were obtained in the form of presenting financial reports in accordance with ISAK 35 standards, namely in the form of Financial Position Reports, Comprehensive Income Reports, Net Asset Change Reports and Cash Flow Reports. It is hoped that this activity can help mosque administrators to better understand the preparation of ISAK 35 standardized financial reports.